Aggregation of sodium salt of ibuprofen and sodium taurocholate mixture in different media: A tensiometry and fluorometry study. (June 2018) - Rub, Malik Abdul; Azum, Naved; Khan, Farah; Asiri, Abdullah M.
Highlights: Aggregation of NaIBU and NaTaC mixtures have been examined. Systems show nonideal behavior. Owing to occurrence of NaCl the cmc values of studied systems increases. N agg and various others related parameters were evaluated. Micropolarity of systems was also obtained. Abstract: Interaction of anionic bile salt sodium taurocholate (NaTaC) and anionic anti-inflammatory drug sodium salt of ibuprofen (NaIBU) in aqueous solutions together with in occurrence of 100 mmmol kg −1 NaCl and 250 mmmol kg −1 urea (NH2CONH2) using tensiometric and fluorometric techniques at 298.15 K temperature has been studied. A tensiometry study disclosed decreasing in surface tension ( γ ) along with critical micelle concentration ( cmc ) of NaIBU and NaTaC mixture, signifying a noteworthy interaction between studied components. Salt decreases the cmc of amphiphiles whereas urea increases their cmc in comparison to the aqueous solution. The solution mixture of NaIBU and NaTaC shows lower cmc value as compared to ideal cmc ( cmc id ) value indicating the non-ideality in the current studied systems. Other parameters regarding tensiometric technique such as micellar mole fraction of mixed micelles/mixed interface ( X 1 m / X 1 σ ), micellar/surface interaction parameter ( β m / β σ ), activity coefficients ( f 1 m / f 1 σ and f 2 m / f 2 σ ) of the mixed micelles/mixed interface, surface excess concentration ( Γ max ), excess Gibbs energy of mixed monolayer/mixed micelle formation ( Δ G ex σ / Δ G ex m ) etc. were estimated. The non-ideality of mixing expressed in terms of the interaction parameter ( β m / β σ ). Various thermodynamic parameters for current systems in all different media were obtained and discussed in detail. The aggregation number ( N agg ), as well as other related parameters regarding fluorescence study, were also evaluated. The higher values of N agg show the being of hydrophobic interactions along with sustains synergism.